Synthesis of nanostructured Vanadium Phosphate catalyste using sonochemical route for partial oxidation of n-butane - Wong Yee Ching; Y.H. Taufiq Yap; J.R. Joshua Hoh (2011)
In this study, sonochemical treatment is used to synthesize nanostructured vanadium pentoxide, V2 O5 with different duration of time and mineralizers. Eight samples of V2 O5 have been prepared using KNO3 and KCI as mineralizers that undergo sonochemical treatment with different duration i.e, 30,60,90 and 120 min,respectively. These samples were donated as KN030, KN060, KN090, KN0120, KC130, KC160,KC190 and KC1120. Nanostructed V2 O5 prepared via ultrasound irradiation for 30 min in KCI (KC130) was chosen as starting material to synthesis vanadium phosphorus oxide catalyst (denoted VP0S30KC1). All the materials synthesized was characterized by using X-Ray diffraction (XRD), Brunauer-Emmett-Teller surface area measurement (BET), chemical analysis,Transmission Electron Microscopy (TEM), Scanning Electron Microscopy (SEM) and temperature programmed reduction(H2-TPR).Catalytic properties for n-butane oxidation of the catalyst, VPOS30KC1 was investigated by using a fixed-bed microreactor at 673 K (GHSV =240h-1).